Upaya Membangun Jiwa Enterpreneurship Bagi Siswa-Siswi SMA Negeri 1 Woyla Timur - Cut Devi Maulidasari; Damrus Damrus; Chairiyaton Chairiyaton; Yayuk Eko Wahyuningsih; Tamitha Intassar Husen (Universitas Teuku Umar, 2022)
An entrepreneur is someone who will carry out an activity smartly and talentedly in introducing a product to consumers and is able to develop a product. It’s important to us know about the condition of the people of the State of Indonesia to this day is abundant with a wealth of natural resources, therefore, as a society with education, do not only look for work but also must be able to create jobs by means of entrepreneurship. Based on the problems or events above, there are several ways that SMA Negeri 1 Woyla Timur or the school can do to minimize or suppress the number of unemployed in Indonesia, one of which is to provide entrepreneurship education to students from an early age, so that by giving views or directions on entrepreneurship, it is expected students have a high spiritual provision of the concept of entrepreneurship. Observing the various problems mentioned above, the Community Service implementation team tried to offer a School-Based Entrepreneurship Model to Students with a case study on students of SMA Negeri 1 Woyla Timur. The result of this service activity is that based on this community service activity, it can be concluded that it is best and proper for every student to be given the ability or skill on how to open an effective and efficient entrepreneur.